2015
DOI: 10.1111/dpr.12110
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Income Growth and Poverty: Evidence from Districts in India

Abstract: This article examines the dynamics of the income‐distribution pattern in India during the post‐1991 economic reforms. It considers district‐level per‐capita income data across agriculture, manufacturing, services, and various constituent sub‐sectors, and finds evidence in favour of a uniform process of growth across sectors and regions, which has helped to reduce poverty. In particular, the article finds that growth in agricultural income and access to finance are important for this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…For example, studies have examined poverty variation across states in India (Alkire & Seth, 2015;Baddeley et al, 2006;Dev & Ravi, 2007). Other studies have looked at the variation in deprivations across districts (Banerjee et al, 2015;Chaudhuri & Gupta, 2009). However, a more recent study employing multilevel modelling points to the importance of village level factors, in addition to state-level context, in shaping the distribution of household deprivations across India (Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have examined poverty variation across states in India (Alkire & Seth, 2015;Baddeley et al, 2006;Dev & Ravi, 2007). Other studies have looked at the variation in deprivations across districts (Banerjee et al, 2015;Chaudhuri & Gupta, 2009). However, a more recent study employing multilevel modelling points to the importance of village level factors, in addition to state-level context, in shaping the distribution of household deprivations across India (Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The economic capabilities of farm entrepreneurs, in this paper, includes farm income levels, access to market information, and chances to acquire and use new farm technologies, as well as children’s access to higher education. In studies by Koch [ 51 ] and Banerjee et al [ 52 ], they found that growth in agricultural income can reduce poverty. Therefore, the ability of farm entrepreneurs to increase farm and non-farm earnings is dependent on their economic capability levels.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with the literature on the effect of economic growth on poverty, various studies have revealed that economic growth has been an important driver of poverty reduction (e.g., Banerjee et al, 2015;Bhagwati, 2001;Bourguignon, 2004;Datt and Ravallion, 2002;Dollar and Kraay, 2002;Fosu, 2015Fosu, , 2018Perera et al, 2013;Ravallion, 2004). However, in investigating the factors underpinning the slow pace of poverty reduction between the mid-1980s and the mid-2000s in Brazil, Ferreira et al (2010) have found that economic growth has played a negligible role in Brazil's poverty reduction.…”
Section: Discussion On the Effect Of Economic Complexity On Povertymentioning
confidence: 99%
“…Building on the aforementioned existing empirical literature on the effect of economic complexity, the present article examines the effect of economic complexity on poverty in developing countries through the channels of economic growth, income inequality and economic growth volatility. An extensive literature has shown that these three channels (i.e., economic growth, income inequality and economic growth volatility) can influence poverty rates (e.g., Banerjee et al, 2015;Bhagwati, 2001;Bourguignon, 2004;Datt and Ravallion, 2002;Dollar and Kraay, 2002;Fosu, 2015Fosu, , 2018Perera et al, 2013;Ravallion, 2004). For example, if economic complexity influences positively a country's economic growth (e.g., Hausmann and Hidalgo, 2009), and reduces the prevailing income inequality in this country (e.g., Hartmann et al, 2017), then it can be a potential driver of poverty reduction in that country, in particular if economic growth contributes to lowering poverty rates (e.g., Banerjee et al, 2015;Bhagwati, 2001;Dollar and Kraay, 2002;Fosu, 2015Fosu, , 2018Perera et al, 2013;Ravallion, 2004) and if income inequality is associated with poverty reduction (e.g., Fosu, 2010;Kulkarnia and Gaiha, 2020).…”
Section: Introductionmentioning
confidence: 99%